Achieving 5% 13C nuclear spin hyperpolarization in high-purity diamond at room temperature and low magnetic field - Vladimir Vladimirovich Kavtanyuk; Changjae Lee; Keunhong Jeong; Jeong Hyun Shim (Scientific Reports)
Abstract Optically polarizable nitrogen-vacancy (NV) centers in diamond enable hyperpolarization of 13C nuclear spins at a low magnetic field and room temperature. However, it remains a challenge to achieve a high level of polarization, comparable to that of conventional dynamic nuclear polarization. In this paper, we demonstrate that a 13C polarization of 5%, equivalent to an enhancement ratio of over $$7 × 10^6$$ , can be attained at less than 10 mT. We used a high-purity diamond with an initial nitrogen concentration below 1 ppm, which resulted in a storage time exceeding 100 min. Aligning the magnetic field along [100] increased the number of NV spins involved in polarization transfer by a factor of four. For this orientation, a comprehensive optimization of the magnetic field intensity and microwave (MW) sweep parameters has been performed. The optimum MW sweep width suggests that polarization transfer occurs primarily to the bulk 13C spins through the integrated solid effect, followed by nuclear spin diffusion.